Attentional asymmetries in peripheral vision. - Klatt, Stefanie; Noël, Benjamin; Schrödter, Robin (British Journal of Psychology, 2024)
Previous research on the use of peripheral vision to identify two spatially separated stimuli simultaneously has led to the conclusion that the focus of attention has the form of a symmetric ellipse with a broader expansion along the horizontal compared to the vertical meridian. However, research on pseudoneglect has indicated that attention is not symmetrically distributed to the whole visual field. Here, we test if the attention window is indeed symmetrical with regard to its shape and resolution during peripheral vision. The results indicate that the position of those stimuli relative to the focus of attention influences the ability to identify a given set of stimuli. Specifically, stimuli presented to the left and top of the fixation point were more frequently identified correctly compared to those presented to the right bottom. That is, the attention window is rather not symmetric, which must be considered in future studies on the nature of the focus of attention.